All soft contact lenses are not created equal. Issue 2 (April 2022) - Efron, Nathan; Morgan, Philip B.; Nichols, Jason J.; Walsh, Karen; Willcox, Mark D.; Wolffsohn, James S.; Jones, Lyndon W.
Abstract: Soft contact lenses that have been prescribed by eye care practitioners are sometimes substituted for alternative lenses by unqualified, unregulated and sometimes even fully regulated lens suppliers, in the mistaken belief that there is essentially no difference between different soft lens types. This review considers the implications of inappropriately substituting soft contact lens types in terms of (a) lens properties: surface treatment, internal wetting agents, material, total diameter, back optic zone radius, thickness, edge profile, back surface design, optical design, power, colour (tint) and ultraviolet protection; and (b) lens usage: wearing modality (daily versus overnight wear) and replacement frequency. Potential aspects of patient dissatisfaction and adverse events when prescribed soft lenses are substituted for lenses with different properties or intended usage are considered. Substitution of 15 of the 16 lens properties considered (i.e. except for back surface design) was found to be related to at least one – and as many as six – potential sources of patient dissatisfaction and adverse ocular events. Contact lens are medical devices which are prescribed and fitted; they should never be substituted for another lens type in the absence of a new prescription further to a full finalised fitting, for the simple reason that all soft contact lenses are not created equal. A substituted lens may have properties that results in undesirable consequences in respect of vision, ocular health, comfort and cosmetic appearance, and may be incompatible with the lifestyle of the patient.